Features of the use of cloud-based translation systems in the process of forming information competence of translators - Rostyslav O. Tarasenko; Svitlana M. Amelina; Albert A. Azaryan (Academy of Cognitive and Natural Sciences, 2019)
The current trends in the translator training are shown, which reflect the orientation towards the use of cloud-based automated translation systems. The possibilities of studying cloud-based translation systems in the educational process of training the translator are considered. The role of mastering modern translation tools for forming information competence of translators, particularly technological component, was described. The definition of the list and type of basic translation tools that should be mastered in the studying process was discussed. These tools should include automated translation systems and terminological management systems. It is advisable to provide for the study of both desktop and cloud-based systems. The inclusion in the content of the training translators the study of cloud-based systems of automated translation after desktop systems is proposed. A number of advantages of cloud-based translation systems for the use in the process of training the translators is defined and substantiated. A comparative analysis of the functional of cloud-based automated translation systems (Wordfast Anywhere, XTM Cloud, and MemSource) with the aim of including them in the content of the training program for translators has been carried out.